1997
DOI: 10.1093/ndt/12.11.2318
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma leptin/fat ratio in patients with chronic renal failure: a cause of malnutrition?

Abstract: Our data suggests that leptin is markedly increased in some patients with chronic renal failure. The association of increased leptin with low protein intake and loss of lean tissue is consistent with leptin contributing to malnutrition but a definitive role cannot be substantiated by this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
1
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 9 publications
4
67
1
2
Order By: Relevance
“…It should be stressed that many protein-bound uremic solutes have important pathophysiologic actions and might be subject to a similar enhancement of toxicity in the case of hypoalbuminemia. Candidate molecules are indoxyl sulfate (6,33,34 ), indole 3-acetic acid (35,36 ), 3-carboxy-4-methyl-5-propyl-2-furanpropionic acid (37,38 ), phenol (39 ), advanced glycation end products (40 -42 ), leptin (43,44 ), homocysteine (45,46 ), hippuric acid (47,48 ), and p-hydroxyhippuric acid (49,50 ).…”
Section: Discussionmentioning
confidence: 99%
“…It should be stressed that many protein-bound uremic solutes have important pathophysiologic actions and might be subject to a similar enhancement of toxicity in the case of hypoalbuminemia. Candidate molecules are indoxyl sulfate (6,33,34 ), indole 3-acetic acid (35,36 ), 3-carboxy-4-methyl-5-propyl-2-furanpropionic acid (37,38 ), phenol (39 ), advanced glycation end products (40 -42 ), leptin (43,44 ), homocysteine (45,46 ), hippuric acid (47,48 ), and p-hydroxyhippuric acid (49,50 ).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that weight loss and anorexia in chronic wasting diseases might be linked with leptin. The ESRD patients are associated with hyperleptinemia, suggesting hyperleptinemia stimulated feedback inhibition (Nordfors et al 1998) as a cause of anorexia and decreased food intake (Young et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Thus we used the leptin/ fat ratio in most of our analyses. Similarly, in the study by Young et al, the leptin / fat mass ratio was used and found as an important indicator of malnutrition (9).…”
Section: Discussionmentioning
confidence: 99%